A Feasibility Randomized Controlled Trial of a Parenting Intervention Offered to Women With Severe Mental Health Problems and Delivered in a Mother and Baby Unit Setting: The IMAgINE Study Outcomes - Wittkowski, Anja; Emsley, Richard; Bee, Penny E.; Camacho, Elizabeth; Calam, Rachel; Abel, Kathryn M.; Duxbury, Paula; Gomez, Paula; Cartwright, Kim; Reid, Holly E. (Frontiers in Psychiatry, 2022)
Background: Approximately 1-2% of mothers may experience severe mental illness (SMI) requiring admission to an inpatient Mother and Baby Unit (MBU). MBUs aim to provide mental health assessment and treatment and strengthen the mother-infant relationship, essential for infant development. Whilst MBUs offer various interventions, they do not routinely offer structured parenting interventions. The Baby Triple P Positive Parenting Program (BTP) was developed to enhance parenting competence, psychological coping and the quality of partner and other social support. Guided by lived experience consultation, we aimed to determine the feasibility and acceptability of delivering BTP plus Treatment as Usual (TAU) in this setting. Method: A multi-site, parallel-group, single-blind pilot randomised controlled trial (registration: ISRCTN12765736) comparing BTP+TAU to TAU in participants, recruited from two MBUs in England. The Baby Triple P intervention consisted of eight parenting sessions, with the final four being delivered over the telephone following MBU discharge. Feasibility outcomes were participant intervention engagement and study retention. Clinical outcomes including maternal parenting competence, bonding and mental health outcomes were assessed at baseline, post-baseline/intervention (10 weeks) and six-month follow-up. Data were analysed using descriptive statistics and linear regression models. An economic feasibility analysis was also conducted. Results: Thirty-seven of the 67 eligible participants consented; 34 were randomised (16 to BTP+TAU and 18 to TAU), of whom 20 were retained at post-intervention data collection and 21 at six-month follow-up. Twelve participants (75%) completed the intervention, which was rated as highly acceptable. Clinical outcomes signalled potential improvements in maternal parenting competence, bonding, mood and mental health symptomatology in participants who received the intervention. Healthcare resource use and EQ-5D-5L questionnaires were well-completed by participants. Delivering BTP in this setting is estimated to cost £443-822 per participant. Conclusions: This is the first trial of a parenting intervention in a MBU setting. BTP is feasible and acceptable to mothers with SMI, with a promising signal for treatment efficacy. Although minor modifications may be required for the collection of observer-rated measures post-MBU discharge, the findings indicate that a larger, definitive trial could be conducted, especially if the setting is extended to include perinatal mental health community settings.